PENGARUH BUDAYA ORGANISASI DAN IMPLEMENTASI KEBIJAKAN PUBLIK TERHADAP KINERJA ORGANISASI PELAKSANA KETERTIBAN, KEBERSIHAN DAN KEINDAHAN DI KOTA BANDUNG - Masana Sembiring (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2019)
The main problem of this research is the organization implementation performance of the orderliness, cleanliness and the beauty at Bandung City of local government has not been optimal. It is thought to be caused by the organizational culture and public policy implementation haven't been done very well , based on Regional Regulation Number 11 2005, about implementation of The Orderliness, Cleanliness and The Beauty ( K3 ) in Bandung City. Method used in this research is a survey method of explanatory type with quantitative approach. The purpose of this research is to analyze and to explain the description of the implementation of organizational culture and public policyimplementation and the influence of organizational culture and public policy implementation simultaneously and partially toward the organization implementation performance of K3. The main instrument which is used for data collecting of this research is a questionnaire, while the interview, documentation and observation as a complementary instrument. The data analysis technique used is SEM statistical technique : Smart PLS software approach. Statistical analysis shows that the influence of organizational culture variable and public policy implementation simultaneously in positively and significantly toward the organization implementation performance of K3 with the percentage of 53.94. It means that other unexamined factors or variables ( epsilon ) give influence with the percentage of 46.06. which are not studied . Organizational culture variable partially has given positive and significant influence toward organizational performance with percentage of 18.38 which is reflected by the highest coefficient of correlation ( loading ) characteristic : results orientation (0.890) followed sequentially by the characteristic of : people orientation (0.839),Innovation and risk-taking (0.804), stability (0.800 ), team orientation (0.790) , aggressiveness (0.743) and attention to detail (0, 735). Public policy implementation variable partially has given positive and significant influence toward the organization implementation performance with the percentage of 35,56 which is reflected by the highest coefficient of correlation ( loading ) factor: The Disposition of implementer ( 0.874 ), followed sequentially by the factor of : Inter organizational communication and enforcement activities ( 0.847 ), Standards and objectives ( 0.831), Resources ( 0.786 ), economic , social and political conditions ( 0.777) and the Characteristics of the implementing agencies ( 0,743 ). The research result also shows that the implementation of organizational culture and public policy implementation in descriptiveapproach with positive contribution to the organization implementation performance of K3, but that variables have not been done optimally suitable with their variable dimension optimally. On the other hand shows that the correlation between organizational culture and public policy implementation variables are in a strong category. The Conclusion of this research shows that organizational culture and public policy implementation variables , both simultaneously and partially give influence in positively and significantly toward the implementation organization performace of K3 in Bandung City.The research also shows that the implementation of organizational culture and public policy implementation by descriptive approach are able to increase organizational performance, So it can be interpreted that, if the application of organizational culture and the public policy implementation will be increased, therefore the organization implementation performance of K3 will also rise